Pengembangan Media Pembelajaran Matematika Berbasis Game Interaktif Menggunakan Aplikasi Adobe Flash CS3 pada Materi Pokok Trigonometri Kelas X SMKN 10 Surabaya - Siti Wulandari; Chusnal Ainy; Endang Suprapti (Universitas Muhammadiyah Surabaya, 2017)
This study aims to develop mathematics media learning based interactive games Adobe Flash CS3 application was valid, practical, feasible and effective. This research was a development research with reference to ADDIE development model (Analysis, Design, Development, Implementation and Evaluation).The subjects of this study were teacher and students of class X SMKN 10 Surabaya. The data obtained by this research were (1) validation of media expert, (2) validation of material expert (3) teacher evaluation, (4) student response questionnaire and (6) mastery of student learning result.The result of media expert validation showed that the learning media developed was valid because the average score of the 82.6% aspect in the category (Very Good) and validation of the material expert was also valid with the average of 82.9% in the category (very good) . Practically defined by the Media Expert by category (feasible for field trials with appropriate revisions) and the Material Expert category (Eligible for trial without revision) as well as from teacher and student activities in the (excellent) category. It was declared worthy of the three Teachers with a total score of 81% (good) as well as a questionnaire for the response of students of large group trials with an average of 3.3 (very good). Students responded very well as many as 56.67% and 43.33% responded well and 90% of students in the class had already fulfill the KKM. So it was declared effective because the media had been said to be valid, practical, feasible and 90% of students complete study in the classroom.